Abstraction, ensemble, and disaggregation approaches to estimate evapotranspiration for use in hydrologic models. (February 2019) - Ranjit Kumar, M; Meenambal, T; Kumar, V
Evapotranspiration (ET) is the most dominant hydrologic process in water balance, yet it is difficult to measure in a watershed. This feature of ET has resulted in the development of many ET equations to estimate ET indirectly. While developing the Watershed Processes Simulation (WAPROS) model, the need for incorporating a good ET procedure is keenly felt, as the main objective is to simulate water balance of the watershed. Among many alternatives, ensemble estimate procedure is selected, for which six ET equations have been chosen. As the input data requirement for ET equations are highly demanding, the ET equations have been modified to dispense with some unimportant data, retaining the validity of the estimate. The details of selected ET equations and the method of ensemble are discussed. The method of disaggregation of potential ET into potential evaporation and potential transpiration has been discussed. As the WAPROS model has been planned as an hourly simulation model, the method of disaggregation of daily ET data into hourly ET data also assumed more importance. In this model, hourly distribution of potential values has been disaggregated into 24 hours for evaporation and 12 hours (daylight) for transpiration. As measured data for actual ET are not available, simulated ET data cannot be compared directly. It requires comprehensive sensitivity analysis of ET equations and estimate of the ensemble method. The sensitivities of ET and hydrologic processes to changes in air temperature are also incorporated. New metrics to aid in sensitivity analysis have been introduced to capture the quantum of changes.